Zdrowie i choroba w Sieci – o przejawach i konsekwencjach popularyzacji wiedzy medycznej w Internecie - Wieczorkowska, Magdalena (Człowiek i Społeczeństwo, 2015)
The article describes the process of the medicalization of cyberspace. The first part of the article depicts the process of medicalization itself and within its frames cybermedicalization is presented. The second part characterizes the medicalization of cyberspace through its aspects and main dimensions: medical portals, virtual health communities, health promotion in cyberspace, illegal medicines and organs trafficking, and the advertising of drugs and medical products in the net and cyberchondria. The last part shows the main consequences of this phenomena.